Biomass and carbon storage in trees of the first section of Chapultepec Park, Mexico City - López-López, Stephanie Fabiola; Martínez-Trinidad, Tomás; Benavides-Meza, Héctor Mario; García-Nieto, Moisés; Ángeles-Pérez, Gregorio (Instituto de Ecología, A.C., 2018)
In recent years, there has been a growing interest in quantifying carbon stocks in urban forests in order to assess their potential in climate change mitigation. In the present study the aboveground biomass and C pools were estimated at the first section of the Chapultepec Park and its relationship with the basal area and species composition was analyzed. Carbon stock of this green area is expected to be important, at least with respect to local neighborhood’s emissions of CO2. For Fraxinus uhdei, the dominant species, biomass estimates generated in natural and urban equations were compared with those obtained in seven trees sampled at the site; the urban equation produced the best estimates. Based on inventories of 27.3% of the green areas of the first section and the use of allometric relationships, the total reservoir was estimated at 24 217 Mg of biomass and 11 226 Mg of C. The species composition and basal area significantly influenced biomass and C pools. The average C content was relatively high compared with those indicated in urban forests in other cities in the world, thus Chapultepec Park can be considered an important reservoir.